Measuring consumer based brand equity sportswear market in Malaysia - Mohd. Israil, Khaliq Ahmad; Islam, Rafikul (s.n, 2012)
Today's sportswear industry is booming in Malaysia. Sportswear items became a common and popular category of consumer goods as it gives young people a more relaxed lifestyle and greater comfort. Consumers wear athletic apparel not only in sports activities alone, but also at home, in school, at work, or at leisure time. Therefore, this study discusses why sportswear brand equity is important for the Malaysian Muslim consumers. This study is also concerned with comparing a range of different brands since a consumer based brand equity measures with the intention to buy and trying to determine how a brand performed in sportswear industry. An important, dimension of this research is highlighted on the existing Muslim consumer behavior and measures the Muslim youth brand loyalty vis-à-vis traditionally used measures in the sportswear market in Malaysia. The purpose of this research is to investigate how the Muslim consumers are influenced by factors of brand equity (perceived quality, brand awareness, brand association, brand loyalty, and halal branding) towards sportswear brands in the country. This study also focuses on the study of brand equity in the context of Malaysian environment, followed by the results to obtain accurate use of information based on the research findings and analysis for marketing decisions by the sportswear products.